Endoscopic endonasal repair of sphenoid cerebrospinal fluid leak, review and institutional experience - Al-Jazeeri, Isra; Al-Jazeeri, Hassan; Al-Momen, Ali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Rhinogenic CSF leaks are not an uncommon presentation. Considering the possibility of drastic intracranial complications if left untreated, makes the management of such cases of outmost importance. Most of the non-traumatic CSF leaks will need a surgical repair. And since the introduction of the endoscopic nasal surgeries, these repairs are done almost always through the endoscopic endonasal approach. Methods: Retrospective review of cases with endoscopic repair of sphenoid CSF leak, who presented to King Fahad Specialist Hospital in Dammam (KFSH-D), from November 2003 to December 2017. And the U.S. National Library of Medicine (Pubmed) database was searched for “Sphenoid CSF Leak”. Results: We had a total of 12 cases. The demographic data, diagnostic investigations and operative data were retrieved and reviewed. Conclusions: We advise using high resolution CT and intra-operative fluroscein for a reliable localization. And we found no complications with use of correct concentration of fluroscein. Endoscopic endonasal approach for repair of sphenoid CSF leak was found to be both effective and safe.